Use of inferior mesenteric vein as an interposition graft for distal renal shunt – A case report - Fábio César Miranda Torricelli; Fábio Crescentini; Beimar Zeballos; Huda Maria Noujaim; Marcelo Perosa de Miranda; Tércio Genzini (Einstein (São Paulo), 2007)
Upper digestive bleeding due to rupture of esophageal varices is asevere complication of portal hypertension in cirrhotic patients. Whenit is associated with portal vein thrombosis, transjugular intrahepaticportosystemic shunt or endoscopic procedures are difficult and lesseffective. In this situation, splenorenal shunt is a good alternative.The aim was to discuss a distal splenorenal shunt with autologousinferior mesenteric vein graft. We report a case of a male patient, 52years old, suffering from alcoholic hepatic cirrhosis and portal veinthrombosis. He had nine episodes of upper digestive bleeding, in spiteof endoscopic treatment. His hepatic function remained good and distalsplenorenal shunt was chosen as the best therapeutic option. Theinferior mesenteric vein was used as an interposition graft for distalrenal shunt due to unexpected events during splenic vein dissection.Postoperative recovery went uneventfully.